A systematic review of mental health interventions to reduce self-stigma in medical students and doctors - Bannatyne, Amy Jean; Jones, Cindy; Craig, Belinda M.; Jones, Dominique; Forrest, Kirsty (Frontiers in Medicine, 2023)
Background A growing body of literature has revealed that many medical students and doctors do not seek professional help for their mental health due to fear of stigma (both public- and self-stigma) and questioning of their clinical competency. The aim of this systematic review was to identify and evaluate direct and indirect interventions that address mental health stigma in medical students and/or doctors. We focused explicitly on studies that measured the impact on self-stigma outcomes. Method A systematic search of the following electronic databases was undertaken from inception to 13 July 2022: PubMed, Embase, PsycINFO, and CINAHL, together with manual searching of reference lists. Screening of titles, abstracts, and full texts of eligible studies, plus quality appraisal using the Mixed Methods Appraisal Tool, were independently conducted by multiple reviewers with disagreements resolved via discussion. Results From 4,018 citations, five publications met the inclusion criteria. None of the studies explicitly aimed to reduce self-stigmatisation, with the majority focusing on medical students. Most of the identified interventions focused on reducing professional stigma (i.e., stigma toward patients with mental illness) and measurement of self-stigma was incidentally collected via a subscale of the general stigma measure selected. Three studies found significant reductions in self-stigma following the delivered intervention. These studies were of moderate quality, had medical student samples, employed combined education and contact interventions, and used the same outcome measure. Discussion Intentional development and evaluation of interventions specifically designed to decrease self-stigma among doctors and medical students are needed, with further research required on the optimal components, format, length, and delivery of such interventions. Researchers delivering public/professional stigma reduction interventions should strongly consider measuring the impact of such interventions on self-stigma outcomes, using fit-for-purpose, psychometrically sound instruments.